Pelatihan Pembuatan Media Pembelajaran Inovatif Kelompok Guru SDN Melong Mandiri 4 Kota Cimahi - Ahmadi f, Yusep; Kadarisma, Gida (Jurnal Pemberdayaan Masyarakat, 2020)
Learning in primary schools largely depends on the role of the teacher, because at the elementary school age students still tend to need teachers as a source of knowledge and direction in solving a problem. Learning in partner primary schools has problems relating to instructional media especially Indonesian language learning media and mathematics. This stimulus community partnership program aims to provide solutions to problems in the partner school of Public Elementary School of Melong Mandiri 4 Cimahi so that the teachers become skilled at designing and making learning media. These problems include the unavailability of adequate learning media; the teacher's skill is not optimal in designing and making innovative learning media. The solution offered in this program is training in designing and making innovative and interesting learning media on Indonesian language and mathematics lessons, namely takalintar media, geoboard, serial images, paper puppets, KPK boards and FPB, for ICT-based media using Powerpoint and Geogebra. This training was conducted using lecture and discussion methods as well as the practice of making instructional media. The results achieved from this activity are there is an increase in the skills of teachers in making innovative learning media by 40%.